Shakespeare Suppressed: The Uncensored Truth about Shakespeare and His Work by Katherine Chiljan - Roper, David L. (Journal of Scientific Exploration, 2012)
In 2011, the film Anonymous directed by Roland Emmerich focused worldwide attention upon what has long been suspected to be a literary and historical conspiracy—the Shakespeare authorship question. Particularly during the last century, scholars from diverse parts of Europe and America have emerged in increasing numbers to voice their doubt that William Shakespeare was ever more than a front for the true author. Mainstream scholarship has largely responded with silence to these protests, but this has only served to sharpen interest, and to reveal the absence of any probative evidence that is sufficient to establish Shakespeare’s authorship. As Hugh Trevor-Roper pointed out, he has been subjected to the greatest battery of organized research that has ever been directed upon a single person. Armies of scholars formidably equipped, have examined all the documents which could possibly contain at least a mention of Shakespeare’s name. . . . And yet the greatest of all Englishmen, after this tremendous inquisition, still remains so close to a mystery that even his identity can still be doubted. (Trevor-Roper 1962) The author, Katherine Chiljan, is a historian who graduated from UCLA, and who can lay claim to more than twenty-five years experience associated with the problem of Shakespeare’s authorship. During that time, she has debated the problem at the Smithsonian Institution, read papers at conferences in both the US and the UK, and served as editor of the quarterly Shakespeare Oxford Newsletter. It is against this background that her book seeks to piece together a jigsaw puzzle depicting the man she calls “the great author”: a man whom she believes to be responsible for writing the works of Shakespeare. It is a daunting task, mainly because there are so many important pieces missing from the puzzle. Whereas the mainstream academic can write from the high ground, and give good accounts of Shakespeare’s life and business transactions, into which he or she inserts at regular intervals of convenience the author’s works, according to their supposed dates of composition, this approach is not open to the unconventional scholar. Chiljan’s first task is therefore to undermine the evidence supporting Shakespeare, in order to create an opening for the true author to appear.